Conditioned place preference for social interaction in rats: contribution of sensory components - Kummer, Kai; Klement, Sabine; Eggart, Vincent; Mayr, Michael J.; Saria, Alois; Zernig, Gerald (Frontiers in Behavioral Neuroscience, 2011)
A main challenge in the therapy of drug dependent individuals is to help them reactivate interest in non-drug-associated activities. We previously developed a rat experimental model based on the conditioned place preference (CPP) paradigm in which only four 15-min episodes of social interaction with a gender- and weight-matched male Sprague Dawley rat (i) reversed CPP from cocaine to social interaction despite continuing cocaine training and (ii) prevented the reinstatement of cocaine CPP. In the present study, we investigated which of the sensory modalities of the composite stimulus 'social interaction' contributes most to the rats’ preference for it. If touch was limited by steel bars spaced at a distance of 2 cm and running across the whole length of a partitioning, CPP was still acquired, albeit to a lesser degree. If both rats were placed on the same side of a partitioning, rats did not develop CPP for social interaction. Thus, decreasing the available area for social interaction from 750 to 375 cm² prevented the acquisition of CPP to social interaction despite the fact that animals could touch each other more intensely than through the bars of the partitioning. When touch was fully restricted by a glass screen dividing the conditioning chambers, and the only sensory modalities left were visual and olfactory cues, place preference shifted to place aversion. Overall, our findings indicate that the major rewarding sensory component of the composite stimulus 'social interaction' is touch (tactition).